Vertical peer supervision of consultation: A linguistic exploration of relational hierarchy. Issue 2 (2nd July 2016) - Newman, Daniel S.; Jones, Jamie; Ritter, Chelsea
Abstract : The language used in consultation supervision by one supervisor-in-training (SIT) and five consultant-in-training (CIT) supervisees during one semester of consultation training in a doctoral-level school psychology program is investigated. Exploratory analyses conducted with Linguistic Inquiry and Word Count software measured SIT and CIT use of pronouns, and summary variables of Analytical Thinking, Clout, Authenticity, and Emotional Tone. Patterns of language use in sessions and changes in patterns over time suggest a hierarchical supervision dynamic despite supervision being offered by a fellow trainee. Implications for consultation supervision in a vertical training model are offered.